21st AIAA Applied Aerodynamics Conference 2003
DOI: 10.2514/6.2003-3519
|View full text |Cite
|
Sign up to set email alerts
|

Development of Unsteadiness in a Rotor Wake in Ground Effect

Abstract: The flow field around the rotor in ground effect has been studied using flow visualization and hot-wire anemometry. Two distinctive flow phenomena, recirculation and ground vortex, are observed in the flow visualization. Hot-wire measurement results indicates high intensity of unsteadiness of the flow field with long time scale. The evolution of the ground vortex is better understood from the experimental results. Three different types of velocity fluctuations are observed around the ground vortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…These images are of theatrical fog illuminated by sheets of white light from lamps operating essentially in 16-microsecond pulses. These observations correspond very well with measurements made using laser velocimetry and with light sheet visualization in the wakes of a small single-bladed rotor in hover 6 and a two-bladed rotor in forward flight [8][9][10] . In these facilities, the periodicity of the vortex system was clearly demonstrated by long-exposure still photographs of a strobed laser sheet synchronized with the rotor 6 ; comparisons of single-shot vs. ensemble-averaged laser sheet images of the core 21 particle arrival deficit intervals 21 and particle arrival statistics 6 .…”
Section: Observations On Tip Vortex Persistencesupporting
confidence: 87%
See 1 more Smart Citation
“…These images are of theatrical fog illuminated by sheets of white light from lamps operating essentially in 16-microsecond pulses. These observations correspond very well with measurements made using laser velocimetry and with light sheet visualization in the wakes of a small single-bladed rotor in hover 6 and a two-bladed rotor in forward flight [8][9][10] . In these facilities, the periodicity of the vortex system was clearly demonstrated by long-exposure still photographs of a strobed laser sheet synchronized with the rotor 6 ; comparisons of single-shot vs. ensemble-averaged laser sheet images of the core 21 particle arrival deficit intervals 21 and particle arrival statistics 6 .…”
Section: Observations On Tip Vortex Persistencesupporting
confidence: 87%
“…Applications include the prediction of blade-vortex interaction noise 1,2 , improvement of rotor performance 3,4,5,6,7 , prediction of mutual interaction between wakes, and wake /rotor /airframe interactions involving the main rotor(s), fuselage and tail rotor 8,9 and predicting wake-ground interactions which are important to improve handling qualities and reduce debris hazards in near-ground operation 10 . This paper examines issues related to the formation and the decay of vortices from rotor blades in the light of recent measurements and analyses.…”
Section: Introductionmentioning
confidence: 99%
“…This is a companion paper to Ref. 1, which used laser sheet flow visualization to prove that a steady wake could be obtained at low advance ratio out of ground effect, and that ground proximity increased the unsteadiness. Regimes of flow structure were identified.…”
Section: Introductionmentioning
confidence: 93%
“…The recirculation regime is observed to occur in the range 0⋅4 < μ* < 0⋅7, where the rotor blade tip vortices recirculate in a loop ahead of the rotor disk. This loop is formed as tip vortices pass along the ground ahead of the rotor and then move in an arc upwards and back towards the rotor disk, where reports suggest a re-ingestion of the wake vortices through the rotor disk (5,9,10) , and the recirculation loop has been observed to increase the inflow through the forward portion of the rotor (11) . Examination of the mean flow shows a separation point at the most upstream extent of the recirculation zone, and as advance ratio increases the separation point moves towards the rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the mean flow shows a separation point at the most upstream extent of the recirculation zone, and as advance ratio increases the separation point moves towards the rotor. Using hot-wire anemometry, between 0⋅04 < μ <0⋅06 with the rotor at h/D = 0⋅36 (10) , Saijo et al, observed the separation point to oscillate This assembly was fixed to the end of a long sting attached to a hand-cranked vertical traverse unit, which was placed on the ground so that the rotor disk was nominally in the horizontal plane with the motor above the disk. The rotor support mechanism was not observed to have any measurable effect on the in-flow to the rotor or to the flow field around the rotor.…”
Section: Introductionmentioning
confidence: 99%